2013
DOI: 10.3746/jkfn.2013.42.6.837
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Sasa borealis on Mechanisms of Adipogenesis

Abstract: Sasa borealis is a major source of bamboo leaves used for traditional medicine in Korea. Obesity is a serious health problem in industrialized countries that has been implicated in various diseases, including type 2 diabetes, hypertension, cancer, and coronary heart disease. Recent reports have proposed mechanisms to reduce obesity by decreasing preadipocyte differentiation, and proliferation in 3T3-L1 preadipocyte. The preadipocytes play a key role by differentiation into mature adipocytes and increasing fat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have reported the anti-obesity activity of medicinal herb extracts, and it is important to inhibit adipogenesis for anti-obesity research ( 22 ). Recent studies reported that the anti-adipogenic activities of plant-based material such as amur grape root ( Vitis amurensis Ruprecht), chocolate vine leave ( Akebia quinata D.), and black ginseng ( 23 , 24 ). Furthermore, Shon et al reported that 20 types fruits and vegetables exhibited the anti-obesity effects via inhibition of lipid accumulation in 3T3-L1 adipocytes ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the anti-obesity activity of medicinal herb extracts, and it is important to inhibit adipogenesis for anti-obesity research ( 22 ). Recent studies reported that the anti-adipogenic activities of plant-based material such as amur grape root ( Vitis amurensis Ruprecht), chocolate vine leave ( Akebia quinata D.), and black ginseng ( 23 , 24 ). Furthermore, Shon et al reported that 20 types fruits and vegetables exhibited the anti-obesity effects via inhibition of lipid accumulation in 3T3-L1 adipocytes ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several natural plant extracts have been reported to have anti-adipogenic activities with their bioactive components playing important roles in the inhibition of adipogenesis [23]. Recent studies have reported the anti-adipogenic activities of plant-based materials such as amur grape roots (Vitis amurensis Ruprecht), chocolate vine leaves (Akebia quinata D.), and black ginseng [24,25], which indicate the immense potential of plants as a source of antiobesity compounds. The increased lipid accumulation in 3T3-L1 adipocytes has been observed to be correlated with elevated ROS levels which indicate that the ROS production is closely linked with lipid accumulation in adipocytes [26].…”
Section: Anti-adipogenic Activitymentioning
confidence: 99%